A inovaç\~ao na agricultura brasileira: Uma reflex\~ao a partir da análise dos certificados de proteç\~ao de cultivares - José Eustáquio Ribeiro Vieira Filho; Adriana Carvalho Pinto Vieira (Instituto de Pesquisa Econômica Aplicada (IPEA), 2013)
– The technological and institutional environment influences the way of doing research and the relationships between its participants. Intellectual property is a strategic issue to build the institutional framework of the new technological regime and therefore the dynamics of innovation in agriculture. Since the Protection of Plant Varieties Law (1997), the mechanisms of intellectual property rights have become fundamental to the management of agricultural research and the strengthening of public research, as well as the encouragement of public-private partnerships, or even a partnership between national and multinational companies. The functions of intellectual property rights are: i) ensure the long-term investment in R&D; ii) protect new knowledge and technological innovations; iii) keep a source of strategic information; iv) attract and promote investments in strategic areas; and v) reduce uncertainties in the business environment involving intangible assets. Since Brazil is a strong agricultural producer, the intellectual property system contributes to consolidate dynamic comparative advantages in the agroindustry.
Keywords: C22; C12; C13; 330; innovation; intellectual property rights; protection of plant varieties and agriculture